Inflammation as a therapeutic target in heart failure with preserved ejection fraction - Peh, Zhen Hui; Dihoum, Adel; Hutton, Dana; Arthur, J. Simon C.; Rena, Graham; Khan, Faisel; Lang, Chim C.; Mordi, Ify R. (Frontiers in Cardiovascular Medicine, 2023)
Heart failure with preserved ejection fraction (HFpEF) accounts for around half of all cases of heart failure and may become the dominant type of heart failure in the near future. Unlike HF with reduced ejection fraction there are few evidence-based treatment strategies available. There is a significant unmet need for new strategies to improve clinical outcomes in HFpEF patients. Inflammation is widely thought to play a key role in HFpEF pathophysiology and may represent a viable treatment target. In this review focusing predominantly on clinical studies, we will summarise the role of inflammation in HFpEF and discuss potential therapeutic strategies targeting inflammation.